Densidade e distribuição das espécies do gênero anopheles (diptera: culicidae) e identificação dos agentes etiológicos da malária em sistemas de Mata Atlântica no estado do Espírito Santo, Brasil - Ferreira, Lucas Mendes (2021)
The present study aimed to investigate the abundance, richness, and diversity of anophelines and detect the natural infection by Plasmodium spp. in specimens of the subgenus Kerteszia from two remote areas of the Atlantic Forest, located in the state of Espírito Santo, to better understand the transmission dynamics of the malaria in the region. The entomological collections were performed once a month, from May 2019 to April 2020. Mosquitoes were captured using two types of light traps, Shannon and CDC automatic. The specimens captured were morphologically identified at the species level using entomological keys. After identification, counting, and storage, anophelines belonging to the subgenus Kerteszia were pooled in groups of up to 10 specimens by species, date, trap type, and place of collection and sent to the Laboratory of Protozoology of the Institute of Tropical Medicine of São Paulo for the molecular detection of the presence of Plasmodium spp. The Shannon-Wiener Diversity Index (H’), Simpson Dominance Index (C), and Pielou Equability Index (J) were the tools used to characterize and compare the anopheline fauna of the two explored areas. A total of 1,471 anophelines belonging to three subgenera and 13 species were captured. The most abundant species was Anopheles (Kerteszia) cruzii (87%), followed by Anopheles (Nyssorhynchus) strodei (6%) and Anopheles (Nyssorhynchus) evansae (4.21%). The area of Valsugana Velha – where cases of malaria are reported sporadically – recorded greater abundance (1,438 specimens) and greater richness (10 species). Molecular techniques confirmed the natural infection of A. (K.) cruzii and Anopheles (Kerteszia) homunculus by Plasmodium spp. Anopheles (Kerteszia) cruzii, due to its abundance, dispersion, and record of natural infection confirmed that it is the main species involved in the transmission of malaria in areas of the Brazilian Atlantic Forest.